Detecting and correcting for heteroscedasticity / Teoh Sian Hoon - Teoh, Sian Hoon (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2007)
The discussion of this paper focuses on detecting the presence of heteroscedasticity using two methods simultaneously: (1) a graph of the residuals versus the independent variable, and (2) Goldfeld- Quandt test. These two methods were applied for the accuracy of detecting heteroscedasticity. Weighted least squares was used in correcting the presence of heteroscedasticity. A clear picture on detecting and correcting heteroscedasticity was discussed in a case study. SPSS was used in plotting the graph of residuals against the independent variable and also in analyzing data using weighted least squares.